2003
DOI: 10.1074/jbc.m302850200
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Congenital Disorders of Glycosylation (CDG-Ii) Provides New Insights into the Early Steps of Dolichol-linked Oligosaccharide Biosynthesis

Abstract: Deficiency of GDP-Man:Man 1 GlcNAc 2 -PP-dolichol mannosyltransferase (hALG2), is the cause of a new type of congenital disorders of glycosylation (CDG) designated CDG-Ii. The patient presented normal at birth but developed in the 1st year of life a multisystemic disorder with mental retardation, seizures, coloboma of the iris, hypomyelination, hepatomegaly, and coagulation abnormalities. An accumulation of Man 1 GlcNAc 2 -PP-dolichol and Man 2 GlcNAc 2 -PP-dolichol was observed in skin fibroblasts of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
100
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 39 publications
3
100
2
3
Order By: Relevance
“…Together with the experimentally determined enzyme activity of Alg2 here, one can now postulate that the temperature-sensitive alg2 yeast mutant allows a small extent mannose addition to Man 1 GlcNAc 2 -PP-Dol, because of some residual activity, and thus also results in accumulation of Man 2 GlcNAc 2 -PPDol, which is not the case in the null mutant of R. pussilis. In this argumentation also, results seamlessly incorporate, deriving from the analysis of the enzyme activity from human skin fibroblasts of a patient with a mutation in hAlg2 causing a defect in elongating Man 1 GlcNAc 2 -PP-Dol (21). In this study it was also shown that Man(1,6)ManGlcNAc 2 -PP-Dol tetrasaccharide did not act as acceptor in the patient but was elongated when membranes from control fibroblasts were used as enzyme source, albeit less efficiently than with Man 1 GlcNAc 2 -PP-Dol as acceptor (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Together with the experimentally determined enzyme activity of Alg2 here, one can now postulate that the temperature-sensitive alg2 yeast mutant allows a small extent mannose addition to Man 1 GlcNAc 2 -PP-Dol, because of some residual activity, and thus also results in accumulation of Man 2 GlcNAc 2 -PPDol, which is not the case in the null mutant of R. pussilis. In this argumentation also, results seamlessly incorporate, deriving from the analysis of the enzyme activity from human skin fibroblasts of a patient with a mutation in hAlg2 causing a defect in elongating Man 1 GlcNAc 2 -PP-Dol (21). In this study it was also shown that Man(1,6)ManGlcNAc 2 -PP-Dol tetrasaccharide did not act as acceptor in the patient but was elongated when membranes from control fibroblasts were used as enzyme source, albeit less efficiently than with Man 1 GlcNAc 2 -PP-Dol as acceptor (21).…”
Section: Discussionmentioning
confidence: 99%
“…In this argumentation also, results seamlessly incorporate, deriving from the analysis of the enzyme activity from human skin fibroblasts of a patient with a mutation in hAlg2 causing a defect in elongating Man 1 GlcNAc 2 -PP-Dol (21). In this study it was also shown that Man(1,6)ManGlcNAc 2 -PP-Dol tetrasaccharide did not act as acceptor in the patient but was elongated when membranes from control fibroblasts were used as enzyme source, albeit less efficiently than with Man 1 GlcNAc 2 -PP-Dol as acceptor (21). This latter observation holds also true for the Alg2 transferase from yeast (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SNP located on the upstream of asparagines-linked glycosylation 2 alpha-1,3-mannosyltransferase homolog (ALG2). 29 The ALG2 gene has three alternative transcripts, and the SNP locates at À3522 bp upstream of all three transcripts. The minor allele of this SNP was predicted by the TF search program to create a new cAMP response element-binding (CREB) to the ALG2 promoter.…”
Section: Discussionmentioning
confidence: 99%